2018
DOI: 10.1016/j.cryobiol.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term preservation of freeze-dried rabbit sperm by adding rosmarinic acid and different chelating agents

Abstract: A B S T R A C TFreeze-drying (FD) technique has been applied as an alternative technology to preserve gene resources to allow simple sperm preservation and shipment at 4°C. Nevertheless, DNA sperm might be damaged by mechanical or oxidative stress throughout FD procedure. Therefore, suitable protection to maintain DNA integrity is required. The aim of this study was to determine the effect of rosmarinic acid (RA) as an antioxidant and two chelating agents (EGTA and EDTA) on the DNA integrity of freeze-dried ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…Finally, intact spermatozoa were the largest category in all the three media evaluated, attesting that they adequately protected the cell structure. Moreover, very few spermatozoa with plasma membrane damage were detected, suggesting that chelating agents plus addition of antioxidant treatments preserve DNA integrity as previously reported (Domingo et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Finally, intact spermatozoa were the largest category in all the three media evaluated, attesting that they adequately protected the cell structure. Moreover, very few spermatozoa with plasma membrane damage were detected, suggesting that chelating agents plus addition of antioxidant treatments preserve DNA integrity as previously reported (Domingo et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…Despite this relevant achievement, only a viable puppy was born and hence the need to study the possible factors that compromised the success of the technique. A later study on lyophilized rabbit sperm demonstrated that EDTA preserved DNA integrity of spermatozoa better than EGTA as well as the positive effect of RA supplementation (Domingo et al, ). However, the effect of chelating molecules on the morphology of freeze‐dried sperm is still not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeni et al (2018) showed that supplementation with RA reduced oxidative stress in freeze-thawed bull sperm and increased sperm quality parameters. Domingo et al (2018) showed that the addition of RA and different chelating agents preserved freeze-dried rabbit sperm for a long time. However, when the concentration of RA was too high (more than 100 μmol/L), the sperm quality decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In most freeze-drying studies, the spermatozoa were snap-frozen without any attempt to maintain their membrane integrity (so called 'viability') [e.g. 80,98,99] while in other studies an attempt to obtain viable cells was made by using proper cryopreservation techniques [e.g. 90,100].…”
Section: Drying Spermatozoamentioning
confidence: 99%